84.0k views
0 votes
Find the sum and express it in simplest form.
(-n3 - 8n - 6) + (-8n+ 9n + 3)

2 Answers

0 votes

Look at the attached picture

Hope it will help you...

Good luck on your assignment

Find the sum and express it in simplest form. (-n3 - 8n - 6) + (-8n+ 9n + 3)-example-1
User Michael Du
by
5.0k points
6 votes

Answer:


=-10n-3

Explanation:


(-n3 - 8n - 6) + (-8n+ 9n + 3)\\\mathrm{Remove\:parentheses}:\quad \left(-a\right)=-a\\=-n\cdot \:3-8n-6-8n+9n+3\\Group\:like\:terms\\=-3n-8n-8n+9n-6+3\\\mathrm{Add\:similar\:elements:}\:-3n-8n-8n+9n=-10n\\=-10n-6+3\\\mathrm{Add/Subtract\:the\:numbers:}\:-6+3=-3\\=-10n-3

User Beau Crawford
by
5.3k points